Interchange: The Promise of Digital History. (Journal of American History, 2008)
Information about an online discussion between U.S. social historians regarding the study of digital history is presented. Subjects under discussion include the definition of digital history, primary sources such as blogs, web sites, email, music, historic images, film clips, databases, and the Google project to digitize books.